Systematic advantages of pulsed beams for measurements of correlation coefficients in neutron decay - Märkisch, Bastian (Physics procedia, 2014)
Measurements - of correlation coefficients in neutron beta decay probe the structure of the weak interaction and serve to search for new physics beyond the standard model of particle physics. In this article we describe how pulsed cold neutron beams can be employed to effectively eliminate or control leading sources of systematic uncertainty. As two examples we introduce the existing instrument PERKEO III and the new instrument PERC.